1993
DOI: 10.1021/bi00075a022
|View full text |Cite
|
Sign up to set email alerts
|

An exact general analysis of ligand binding displacement and saturation curves

Abstract: Quantitative analysis of a ligand-protein interaction relates binding to the free concentration of ligand molecules in solution. A theoretical analysis is presented herein, by which intermolecular interactions can be described as a function of the added concentrations of ligand molecules. Following this analysis, ligand binding displacement and saturation curves can be converted directly into a linear form, even when nonradioactively labeled ligands are used to detect the ligand-protein interaction. From the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The conservative substitution of Tyr 29 by a phenylalanine in Notch will have no effect on the binding affinity. The results with E3N4E/MYA, furthermore, show that the remaining hEGF B-loop residues (23)(24)(25)(26)(27)(28) can be replaced by the corresponding Notch residues without loss of receptor binding ability. Notable is the substitution of isoleucine 23 for the positively charged lysine, because many point mutation studies have indicated that this residue can only be replaced by a large hydrophobic residue, whereas smaller and/or more hydrophilic side chains (Ala, Thr, and Asp) decrease the binding affinity considerably (5).…”
Section: C1-----------------------------------------------c6 Ndmentioning
confidence: 88%
See 1 more Smart Citation
“…The conservative substitution of Tyr 29 by a phenylalanine in Notch will have no effect on the binding affinity. The results with E3N4E/MYA, furthermore, show that the remaining hEGF B-loop residues (23)(24)(25)(26)(27)(28) can be replaced by the corresponding Notch residues without loss of receptor binding ability. Notable is the substitution of isoleucine 23 for the positively charged lysine, because many point mutation studies have indicated that this residue can only be replaced by a large hydrophobic residue, whereas smaller and/or more hydrophilic side chains (Ala, Thr, and Asp) decrease the binding affinity considerably (5).…”
Section: C1-----------------------------------------------c6 Ndmentioning
confidence: 88%
“…Bacteria were grown in 2YTE (per liter: 16 g of bactotryptone, 10 g of yeast extract, 8 g of NaCl, 0.4% glucose) at 30°C until an A 600 of 1.5 was reached, and the periplasmic proteins were isolated as described previously (23). The fusion proteins were purified using IgG-Sepharose (Amersham Pharmacia Biotech), and the recovery was measured by an enzyme-linked immunosorbent assay based on binding competition with biotin-labeled protein A (24). The recombinant growth factors were separated from the two IgG binding domains by digestion with Factor X coupled to CNBr-activated Sepharose and further purified by an additional run on IgG-Sepharose.…”
Section: Methodsmentioning
confidence: 99%
“…Expression and Purification of Recombinant Growth Factors-The expression of ZZ/FX/growth factor fusion protein in the periplasm was analyzed by SDS-polyacrylamide gel electrophoresis and Western blotting, and the total amount of IgG binding activity in the periplasm was measured by a competitive enzyme-linked immunosorbent assay (19). The levels of expression of wild type and mutant growth factors appeared to be similar on Western blot as shown in Fig.…”
Section: Mutant Growth Factors-in Previous Workmentioning
confidence: 94%
“…Bacteria were grown in 2YTE (16 g of bactotrypton, 10 g of yeast, 8 g of NaCl/liter) at 28°C until an A 600 of 1.5 was reached and the periplasmic proteins were isolated as described (17). After purification on IgG-Sepharose (Pharmacia), the amount of fusion protein recovered was measured by a competitive enzyme-linked immunosorbent assay using biotin-labeled protein A (19). The fusion proteins were digested by Factor X a coupled to CNBr-activated Sepharose, and the growth factors were purified by an additional run on IgGSepharose.…”
Section: Methodsmentioning
confidence: 99%
“…The yield of purified fusion protein was determined in an ELISA-like binding competition on IgG antibodies using biotinlabeled protein A as competitor (22), while the biological activity of the samples was determined in a binding competition assay with iodinated murine (m)EGF on HER-14 cells (23 …”
Section: Ligand Productionmentioning
confidence: 99%